(untitled) (Eurasian Journal of Ecology, 2016)
Great interest is the use of "internal image" of the antigen, i.e. anti-idiotypic antibodies (AIAB) against Fab-antibody fragments that are specific to ES-AG epitopes. The aim of this research was to determine the possibility of using anti-idiotypes as an antigen in ELISA for serological diagnosis of Opisthorchiasis. To do this, were conducted determine immunochemical properties of anti-idiotype antibodies. The results of research suggest the possibility of using Hybridomas 4H10 as an antigen in the development of immunoassays for the diagnosis of Opisthorchiasis.